2002
DOI: 10.1086/338889
|View full text |Cite
|
Sign up to set email alerts
|

ChandraObservations of NGC 253. II. On the Origin of Diffuse X‐Ray Emission in the Halos of Starburst Galaxies

Abstract: We present a detailed case study of the diffuse X-ray and Hα emission in the halo of NGC 253, a nearby edge-on starburst galaxy driving a galactic superwind. The arcsecond spatial resolution of the ACIS imaging spectroscope on the Chandra X-ray Observatory allows us to study the spatial and spectral properties of the diffuse X-ray emitting plasma, at a height of between 3 and 9 kpc above the disk in the northern halo of NGC 253, with greatly superior spatial and spectral resolution compared to previous X-ray i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
323
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(344 citation statements)
references
References 83 publications
(144 reference statements)
21
323
0
Order By: Relevance
“…Masai et al 2002) and the contamination by point-like, hard sources in the diffuse emission spectrum (e.g. in NGC 253, Strickland et al 2002). Another way to model the high ionization spectrum in terms of a galactic wind, is to invoke quasi-thermal acceleration of electrons which then would produce X-rays with thermal photons.…”
Section: The Nature Of the Fe XXVI Linementioning
confidence: 99%
“…Masai et al 2002) and the contamination by point-like, hard sources in the diffuse emission spectrum (e.g. in NGC 253, Strickland et al 2002). Another way to model the high ionization spectrum in terms of a galactic wind, is to invoke quasi-thermal acceleration of electrons which then would produce X-rays with thermal photons.…”
Section: The Nature Of the Fe XXVI Linementioning
confidence: 99%
“…On the other hand, high angular resolution alone is not enough: recent Chandra studies (Strickland et al 2002;Martin, Kobulnicky, & Heckman 2002) demonstrated that the relatively low spectral resolution of the ACIS detector makes individual element abundance analysis still problematic. The high spectral resolution of the Chandra gratings rapidly degrades for sources that are much more extended than the instrumental point-spread function (PSF), and thus these gratings are almost useless for the study of nearby SB galaxies.…”
Section: X-ray Spectra and Hot-gas-phase Abundancesmentioning
confidence: 99%
“…Naturally, most of the work on this topic has been concentrated on edge-on disk galaxies, which allow for detection of extraplanar gas unambiguously. Vertical X-ray plumes are detected along the minor axes of many nuclear starburst galaxies (e.g., NGC 253, Strickland et al 2002;NGC 3079, Cecil et al 2002;NGC 4945, Weaver 2001;M82, Lehnert, Heckman, & Weaver 1999 , Fig. 4).…”
Section: Hot Gas Outflows From Nuclear Starburst Galaxiesmentioning
confidence: 99%
“…Deep X-ray observations of nuclear starburst galaxies have further revealed large-scale, low surface brightness diffuse X-ray halos, which seem to be confined within faint limb-brightened Hα-emitting boundaries (e.g., NGC 253, Strickland et al 2002;NGC 1569, Martin et al 2002M82, Lehnert et al 1999, Fig. 4).…”
Section: Hot Gas Outflows From Nuclear Starburst Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation